2019
DOI: 10.25179/tjem.2018-63015
|View full text |Cite
|
Sign up to set email alerts
|

Relation Between Night Eating Syndrome and Academic Grades Among University Students

Abstract: Objective: Night eating syndrome refers to a condition, characterized by night hyperphagia and nocturnal ingestions that are often accompanied by an altered sleep and mood pattern. It is very common among students, who become prone to night eating syndrome owing to sleep deprivation and nocturnal eating habits. Adherence to such behavior increases the chances of poor higher mental function and an altered circadian rhythm, eventually resulting in compromised learning and academic failures. The present study int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…While the caloric distribution by mealtime is adequate, the fact that students consume an average of 120 kcal/day in latenight snacks is concerning. Ahmad et al discovered that late-night snacking is linked with an increase in BMI and a decline in grade point average among university students (14).…”
Section: Discussionmentioning
confidence: 99%
“…While the caloric distribution by mealtime is adequate, the fact that students consume an average of 120 kcal/day in latenight snacks is concerning. Ahmad et al discovered that late-night snacking is linked with an increase in BMI and a decline in grade point average among university students (14).…”
Section: Discussionmentioning
confidence: 99%
“…In studies of convenience samples of university students, the prevalence based on the NEDQ was reported to range from 1.2% [16] and 2.4% [14] to as high as 5.7% [9]. In a study of Turkish university students, 9.5% met the criteria for NES based on the NEDQ [17]. The only study of a national convenience sample of adults using the NEDQ found a prevalence of 9.4% [7].…”
Section: Methodsmentioning
confidence: 99%
“…Eating right and eating timely is one of the biggest busters to deal with stress and obesity. [ 67 ]…”
Section: Mindfulness Intervention For Stress Eating To Control Obesitymentioning
confidence: 99%